2019
DOI: 10.1002/jimd.12166
|View full text |Cite
|
Sign up to set email alerts
|

Free urinary glycosylated hydroxylysine as an indicator of altered collagen degradation in the mucopolysaccharidoses

Abstract: Extracellular matrix (ECM) disruption is known to be an early pathological feature of the Mucopolysaccharidoses (MPS). Collagen is the main component of the ECM and its metabolism could act as a useful indicator of ECM disruption. We have measured the specific collagen breakdown products; urinary free hydroxylated (Lys‐OH) and glycosylated hydroxylysines (Lys‐O‐Gal and Lys‐O‐GalGlc) in MPS patients using a tandem liquid chromatography tandem mass spectrometry assay. A pilot study cohort analysis indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Heywood analyzed urine samples from GAG-positive MPS I, MPS II, and MPS VI patients by label-free proteomics, followed by a targeted proteomic multiple reaction monitoring LC-MS/MS assay; the study evidenced several differentially expressed proteins implicated in extracellular matrix organization, some of which allowed the researchers to differentiate between the MPS II neurological and non-neurological phenotype [244]. Later, the same group measured, by using the LC-MS/MS method, the levels of different forms of urinary hydroxylysine, as indicators of altered collagen metabolism and hence potential biomarkers of MPS disease [258]. A different proteomic approach based on two-dimensional gel electrophoresis combined with MALDI-TOF/TOF was used to identify the differential protein profile in the urine of MPS II patients [259].…”
Section: Disease Biomarkersmentioning
confidence: 99%
“…Heywood analyzed urine samples from GAG-positive MPS I, MPS II, and MPS VI patients by label-free proteomics, followed by a targeted proteomic multiple reaction monitoring LC-MS/MS assay; the study evidenced several differentially expressed proteins implicated in extracellular matrix organization, some of which allowed the researchers to differentiate between the MPS II neurological and non-neurological phenotype [244]. Later, the same group measured, by using the LC-MS/MS method, the levels of different forms of urinary hydroxylysine, as indicators of altered collagen metabolism and hence potential biomarkers of MPS disease [258]. A different proteomic approach based on two-dimensional gel electrophoresis combined with MALDI-TOF/TOF was used to identify the differential protein profile in the urine of MPS II patients [259].…”
Section: Disease Biomarkersmentioning
confidence: 99%
“…Creatinine concentration was measured for each urine sample using mass spectrometry as previously described [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding bone remodeling biomarkers, osteocalcin was found to be increased in children with MPS disorders, and BSAP and urinary PYD showed an increasing trend, which suggested increased osteoblast activity. Plasma IL-1β, TNF-α, and D-PYR (which were higher in MPSIthan in controls [ 58 ] and IL-6 might also be appropriate biomarkers to monitor progression in joint contracture, short stature, and hip dysplasia over time [ 59 ] ( Table 2 ).…”
Section: Biomarkers Related To Bone Metabolism In Mpsmentioning
confidence: 99%
“…Patel et al recently reported that urinary-free hydroxylated (Lys-OH) and glycosylated hydroxylysines (Lys-O-Gal and Lys-O-GalGlc) in MPS patients measured by tandem liquid chromatography-tandem mass spectrometry assay were indicators of altered collagen degradation [ 59 ]. These are unique and specific post-translational modifications of collagen [ 63 ].…”
Section: Biomarkers Related To Bone Metabolism In Mpsmentioning
confidence: 99%
See 1 more Smart Citation